2019
DOI: 10.3390/ijms20071589
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Mammalian Aquaporin Water Channels

Abstract: Aquaporins (AQPs) are water channel proteins that are essential to life, being expressed in all kingdoms. In humans, there are 13 AQPs, at least one of which is found in every organ system. The structural biology of the AQP family is well-established and many functions for AQPs have been reported in health and disease. AQP expression is linked to numerous pathologies including tumor metastasis, fluid dysregulation, and traumatic injury. The targeted modulation of AQPs therefore presents an opportunity to devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 144 publications
(228 reference statements)
1
95
0
3
Order By: Relevance
“…The majority of aquaporins are modulated by at least one metal ion [2,76,77]. Mercury especially has been shown to have an inhibitory effect on almost all AQPs, with the exception of AQP6 to which it has an activating effect [78].…”
Section: Metal Ion Mediated Regulation Of Aqp4mentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of aquaporins are modulated by at least one metal ion [2,76,77]. Mercury especially has been shown to have an inhibitory effect on almost all AQPs, with the exception of AQP6 to which it has an activating effect [78].…”
Section: Metal Ion Mediated Regulation Of Aqp4mentioning
confidence: 99%
“…Aquaporins (AQPs) are a group of selective transmembrane channels which are expressed in every major organ group in the human body [1,2]. While 13 unique AQPs have been identified in the human body thus far, aquaporin-4 (AQP4) has become an interesting therapeutic target in various neurological disorders, due to its variety of functions and widespread expression in the nervous system [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These protein water channels are inserted into the apical membranes of tubular epithelial cells where they enhance the ability of tubules to reabsorb water, thus conserving it. Although we did not measure AVP, aquaporins, or related compounds in this experiment, our speculation is reasonable because it is based on irrefutable, supporting evidence [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 80%
“…Several inhibitors have been identified that are more or less effective in inhibiting AQPs, such as the small molecule inhibitors, TEA and acetazolamide, which can selectively and reversibly inhibit AQP1 and -4 isoforms (Abir-Awan et al, 2019). The recently discovered molecules, DFP00173 and Z433927330 that have been shown to block glyceroporins by reducing channel glycerol permeability (Abir-Awan et al, 2019). Among the heavy metal ions, Cu ions, NiCl 2 and gold compounds proved to be effective in inhibiting AQP3 (Aikman et al, 2018).…”
Section: Inhibitors and Therapeutic Perspectivesmentioning
confidence: 99%